Viral Infections and Temporal Programming of Autism Spectrum Disorders in the Mother's Womb - Jash, Sukanta; Sharma, Surendra (Frontiers in Virology, 2022)
Recent reports have suggested a tight relationship between viral infections and neurodevelopmental disorders. In this regard, tissue damage can be caused by direct viral infection or induced immune responses and cytokine storm. Although recent years have seen phenomenal progress in diagnosing autism spectrum disorders (ASD) and identifying genetic and epigenetic causative factors contributing to this group of neurodevelopmental disorders, almost 60% cases in children remain of unknown etiology. Little is known about the collective pathophysiology of ASD. In this regard, epidemiological data suggest that viral infections during pregnancy are associated with high risk of having an autistic child. Although in-depth and longitudinal studies are still awaited, recent predictions and early studies suggest that SARS-CoV-2 infection during pregnancy may also contribute to the onset of autism-like features in the offspring or impact autistic individuals. We hypothesize that ASD are programmed in the mother's womb and that uterine, not peripheral, immune activation is the initial trigger to induce fetal brain developmental anomalies. We further hypothesize that exposure to infections only during a temporal window of pregnancy impact the onset of ASD-like pathology, particularly in the male fetus/offspring. We will discuss the role of uterine regulatory T cells and their inflammatory trans-differentiation in the pathophysiology of ASD and comment on possible therapeutic intervention options.